2021
DOI: 10.3390/nano11092371
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Functionalized Fe3O4@SiO2 Core-Shell Magnetic Nanoparticles for Dye Adsorption

Abstract: Fe3O4@SiO2 core-shell nanoparticles (NPs) were synthesized with the co-precipitation method and functionalized with NH2 amino-groups. The nanoparticles were characterized by X-ray, FT-IR spectroscopy, transmission electron microscopy, selected area electron diffraction, and vibrating sample magnetometry. The magnetic core of all the nanoparticles was shown to be nanocrystalline with the crystal parameters corresponding only to the Fe3O4 phase covered with a homogeneous amorphous silica (SiO2) shell of about 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…400), ( 422), (511), and (440), indicating that they had face-centered cubic structures. 69 The broadband at about 22°w as due to the amorphous peak generated by the amorphous SiO 2 . 70,71 These results indicate that core−shell nanoparticles were successfully synthesized without destroying the crystal structure of Fe 3 O 4 cores during SiO 2 coating and surface functionalization.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…400), ( 422), (511), and (440), indicating that they had face-centered cubic structures. 69 The broadband at about 22°w as due to the amorphous peak generated by the amorphous SiO 2 . 70,71 These results indicate that core−shell nanoparticles were successfully synthesized without destroying the crystal structure of Fe 3 O 4 cores during SiO 2 coating and surface functionalization.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the existing literature, composite microgels exhibited very good adsorption behavior for various pollutants such as heavy metal ions, dyes, pharmaceuticals, etc. Since some composite microgels can be easily synthesized and redeveloped, they have been considered as a promising entrant for wastewater treatment. Adsorption capacity or elimination efficiency of the composite microgels can be tuned by the change of different parameters such as temperature and pH of the solution. On the other hand, efficiency also depends on the use of different constituent materials in composite microgels such as nonpolymeric materials and metals.…”
Section: Applications Toward Environmental Remediationmentioning
confidence: 99%
“…From the previous studies [39], it was reported that the 3-aminopropyltrimethoxysilane (APTS) functionalized Fe 3 O 4 @SiO 2 nanoparticles exhibit a similar spinel structure with the face centered cubic (FCC). Various researchers showed that the (3-aminopropyl)-triethoxysilane (APTES) functionalized Fe 3 O 4 @SiO 2 nanoparticles exhibit a similar spinel ferrite crystal structure [40,41]. The synthesized amino-functionalized Fe 3 O 4 @SiO 2 nanoparticles show spinel ferrite patterns [42].…”
Section: Reusability/regeneration Studiesmentioning
confidence: 99%